MIDDLE EAST AS A GEOPOLITICAL MONITOR OF THE WORLD ORDER - Jankovic, Slobodan (Political Review, 2026)
Author wants to check the claim of the Alexandr Dugin that Middle East is one of the geopolitical monitors of the world. He notes that the war started by Israel and United States against Iran questions and dilutes all notions of national interest, of democracy building or of international society in international relations, of institution building, of conflict over markets, regional order construction (without any consensus of at least the majority of regional countries), and the struggle for the class domination. What remains are religious or transcendental motives of the decision makers, and that is why he tries to understand this war and its consequences from the philosophy of history angle. Thus, he emphasizes the role of agent, or of governing elites as main shapers of international relations. In order to sustain this he presented the pluridecennial effort of US to sustain Israel defence budget and its security also by donating to Arab countries, in order for them to be in good relations with Jewish nation state. Military actions harmed strategic economic infrastructural interests also of USA, EU and Israel, thus confirming the supremacy of other motives over economy. Furthermore, the collapse of the world order is outcome of the failure of China and Russia to preserve it through adaptation from western-led to multilateral management. He contends that they failed in the macro region of the Middle East, due to Israeli American wars in that part of the world. Author finally draws conclusions on the future asset of the world order and destiny of Western alignment. Second chapter delineates importance of the macro region for the great powers, and for international political, legal and financial order. Third chapter briefly reconstructs crucial steps in the change of the world order manifested in regional events since the second half of the 1990s. Next, fourth chapter examines how polarity changes in the region are harbinger of world trends, from the multipolarity in the region already in 2014, US evacuation form Kabul, economic rise of China as a regional partner and other events indicating major trends. Finally, first defeat of Israel and impotence of US to impose the change in Iran are omens of the decline or of overstretch of previously leading great power, and of the instability before the establishment of the new world order.
Keywords: Middle East; multipolarity; Israel; USA; Iran